Simulasi Monitoring Automatic Dosing Sistem pada Mesin Vending Kopi Tubruk pada Kopi Wonosobo - Purnomo, Wahyudi; Adhie Candra, Wahyu; Alfaizi, Muhammad Firdaus (The Indonesian Journal of Computer Science, 2024)
This study proposes an IoT-based system to automate and monitor the Wonosobo coffee-making process. The traditional method, involving manual mixing of coffee and sugar, often yields inconsistent results. The new system, accessible via a smartphone app, aims to improve consistency and quality by replacing human intervention with an automatic filling system. It provides real-time updates and alerts users to dosage discrepancies. The end product is a coffee vending machine with a built-in monitoring system, enhancing efficiency and allowing users to oversee the process remotely. This innovation contributes significantly to the automation technology in the coffee industry.